The electron trap parameter extraction-based investigation of the relationship between charge trapping and activation energy in IGZO TFTs under positive bias temperature stress. (February 2018) - Rhee, Jihyun; Choi, Sungju; Kang, Hara; Kim, Jae-Young; Ko, Daehyun; Ahn, Geumho; Jung, Haesun; Choi, Sung-Jin; Myong Kim, Dong; Kim, Dae Hwan
Highlights: The use of ΔVT de-embedded from the measured PBTS ΔVT which is associated only with the charge trapping into gate insulator. Detailed and clear procedure of extracting the gate insulator electron trap parameters in IGZO thin-film transistors. Analysis of the relationship between activation energy and electron trap parameters. Useful in the joint-optimization of gate insulator and active films in highly stable IGZO thin-film transistors. Abstract: Experimental extraction of the electron trap parameters which are associated with charge trapping into gate insulators under the positive bias temperature stress (PBTS) is proposed and demonstrated for the first time in amorphous indium-gallium-zinc-oxide thin-film transistors. This was done by combining the PBTS/recovery time-evolution of the experimentally decomposed threshold voltage shift (ΔVT ) and the technology computer-aided design (TCAD)-based charge trapping simulation. The extracted parameters were the trap density (NOT ) = 2.6 × 10 18 cm −3, the trap energy level (ΔET ) = 0.6 eV, and the capture cross section (σ0 ) = 3 × 10 −19 cm 2 . Furthermore, based on the established TCAD framework, the relationship between the electron trap parameters and the activation energy (Ea ) is comprehensively investigated. It is found that Ea increases with an increase in σ0, whereas Ea is independent of NOT . In addition, as ΔET increases, Ea decreases in the electron trapping-dominant regime (low ΔET ) and increases again in the Poole–Frenkel (PF) emission/hopping-dominant regime (high ΔET ). Moreover, our results suggest that the cross-over ΔET point originates from the complicated temperature-dependent competition between the capture rate and the emission rate. The PBTS bias dependence of the relationship between Ea and ΔET suggests that the electric field dependence of the PF emission-based electron hopping is stronger than that of the thermionic field emission-based electron trapping.